2009
DOI: 10.1557/proc-1157-e06-02
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Mechanisms of Copper CMP – Passivation Kinetics of Copper in CMP Slurry Constituents

Abstract: During copper CMP, abrasives and asperities interact with the copper at the nano-scale, partially removing protective films. The local Cu oxidation rate increases, then decays with time as the protective film reforms. In order to estimate the copper removal rate and other Cu-CMP output parameters with a mechanistic model, the passivation kinetics of Cu, i.e. the decay of the oxidation current with time after an abrasive/copper interaction, are needed. For the first time in studying Cu-CMP, microelectrodes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The similar Mo SERs and the different Mo RRs at pH 2-8 suggest that the amount of Mo oxides formed during the interval (τ) between sequential mechanical abrasions may be different. This time interval (τ) has been calculated in several studies, [30][31][32] which reported τ to be on the order of milliseconds. To characterize the formation of Mo oxides by H 2 O 2 in milliseconds, chronoamperometry was used.…”
Section: Resultsmentioning
confidence: 99%
“…The similar Mo SERs and the different Mo RRs at pH 2-8 suggest that the amount of Mo oxides formed during the interval (τ) between sequential mechanical abrasions may be different. This time interval (τ) has been calculated in several studies, [30][31][32] which reported τ to be on the order of milliseconds. To characterize the formation of Mo oxides by H 2 O 2 in milliseconds, chronoamperometry was used.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the current density transients I t measured in the similar solutions, containing both the complexing agent such as glycine and the inhibitor such as BTA, should include the non-faradaic double layer charging in addition to the faradaic current. 24,31,32 As a result, I t can be fitted with a double-exponential decay law as follows: 31,32 I t = I f e −t/τ f + I c e −t/τc + I 0 [9] Where I f and I c are the peak responses of the current density from the faradaic reactions and the double-layer charging, respectively. τ f and τ c are the corresponding time constants, separately.…”
Section: Resultsmentioning
confidence: 99%
“…In order to remove the native copper oxides and to prepare a fresh copper surface, the electrode was held at −1.2 V (vs. E Ag/AgCl ) for 60 s as a standard pretreatment procedure for all the electrochemical experiments. 23,24 The OCP experiments were first conducted, and then were followed by the linear sweep experiments, including the potentiodynamic polarization experiments and the cyclic polarization experiments, and the chronoamperometry experiments. Specifically, for the linear sweep experiments, the step height was set to 2 mV and the scan rate was set to 5 mV/s; 25 for the chronoamperometry experiments, the externally applied electrical potential provided a thermodynamic driving force for the oxidation reaction of the fresh copper surface, by which the reaction product could further react with the complexing agent such as glycine and the inhibitor such as 1,2,4-triazole in the solution.…”
Section: Methodsmentioning
confidence: 99%
“…24 Complicating the material removal prediction further is the effect of the chemicallyactive slurry and complex particle-surface interactions which dictate the wear process. [25][26][27][28] Early CMP models began as mostly-empirical, wafer-scale correlations for the global MRR based upon the Preston's equation 29 (Eq. 2) where K p is the empirical Preston's coefficient, P is the applied pressure, and V is the relative velocity between the wafer and the pad.…”
mentioning
confidence: 99%